Purine derivatives excretion and estimation of microbial protein supply on sheep receiving different protein suplements - Asmuddin Natsir (Jurnal Ilmu Ternak dan Veteriner, 2007)
The urinary excretion of purine derivative (PD), which consists of allantoin, uric acid, xanthine and hypoxanthine, was used to estimate Microbial Nitrogen (MN) supply on sheep given oaten hay as basal diet supplemented either with faba beans (faba) or barley fortified with urea (barley-urea). Three growing wethers, with average body weight of 43 ± 2.29 kg, were randomly assigned to one of three experimental diets, i.e. oaten hay without supplement (C), diet C + barley-urea (CB), and diet C + faba (CF), according to latin square design (3 x 3). Results of the experiment indicated that PD excretion for C was lower (P = 0.07) than that of CB and CF (2.84 vs 6.08, 7.67 mmol/d). Absorbed PD and estimation of MN supply for C was less (P = 0.07) than those of CB and CF, namely 1.26 vs 6.64, 8.80 mmol/d and 0.91 vs 4.8, 6.30 g N/d respectively. However, the efficiency of MN synthesis was similar, whether the calculation was based on digestible organic matter fermented in the rumen, DOMR (g MN/kg DOMR, P = 0.20) or based on N intake (g MN/g N intake, P = 0.40). In conclusion, supplementation of oaten hay with different protein supplements may improve the estimation of microbial N supply in the growing sheep but both supplements gave similar results on the estimation of MN supply. Key Words: Purine Derivative, Microbial Protein, Protein Supplement, Sheep